Sintesis Kitosan Dari Limbah Cangkang Kepiting Dengan Variasi Suhu Dan Waktu Pada Proses Deasetilasi - Rusma Yanti; Drastinawati Drastinawati; Yusnimar Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Chitosan is a biopolymer produced from the chitin deacetylation process that is widely present in the outer skin of crustacean animals such as shrimp and crabs. This study aims to determine the effect of temperature and reaction time on the deacetylation process and chitosan characterization analysis (yield, moisture content, ash content, and deacetylation degree). Crab shell crab with size of 100 mesh. The chitin found in the crab shell powder was isolated by deproteinization and demineralization processes. The resulting chitin is then transformed into chitosan by deacetylation process under operating conditions at 100 °C, 110 °C and 120 °C, 50% NaOH concentration, chitin mass ratio and NaOH volume 1:20 (b / v), stirring rate 150 rpm, and reaction time of 1 hour, 2 hours and 3 hours. The results showed that the higher the temperature and the duration of reaction time caused an increase in the degree of deacetylation and a decrease in yield and ash content, while the water content had no effect. Chitosan obtained has a yield of 38.14 - 60.36%, moisture content of 1.78 - 3.57%, ash content 0.75-1.75% and deacetylation degree 72,47 – 86,75%.Keywords: biopolymer, chitin, chitosan, deacetylation, deacetylation degree